Physical education daily stressors and factors: defining teachers and school managers - Simone da Silva Salgado; Fabiano Lange Salles; Cecília Fonseca Pessôa de Andrade Alves (Motrivivência, 2012)
The target of this layout is to present and discuss some aspects of Physical Educationteachers’ working conditions and some defensive strategies that can be used by themto overcome the professional fatigue. The first studies about Burnout dated from 1970.We conclude that, although cannot eliminate school daily stressors factors that takes partdirectly in Physical Education teacher’s actions, we can prevent and it requires a newposture of school management to a change the aim about the discipline and their needs.